Animal cell cultures: Risk Assessment and biosafety recommendations - Katia Pauwels; Bernadette Van Vaerenbergh; Chuong Dai Do Thi; Berghmans,L.; Geneviève Waeterloos; Van Bockstaele,D.; Dorsch-Hasler,K.; Myriam Sneyers (Appl.Biosaf., 2007)
During the last three decades, animal cell culturing hasbeen essential for biomedical research and biotechnologicalactivities in general. Along with this increasing importance,biosafety concerns have pointed to the risks of manipulatinganimal cell cultures for human health and the environment. Amaximal reduction of these risks necessitates a thorough riskassessment of the cell cultures used. It involves an evaluationof both the intrinsic properties of the cell culture, includingsubsequent properties acquired as a result of genetic modification,and the possibility that the cell culture may inadvertentlyor deliberately become contaminated with pathogens.The latter is a major hazard associated with the manipulationof animal cell cultures, as adventitious agents may be pathogenicand have a better capacity to survive in unfavorableconditions. Consequently, most of the containment measuresprimarily aim at protecting cells from adventitious contamination.Therefore, a comprehensive evaluation of the risks encounteredduring the handling of cell cultures should includeconsiderations regarding the type of manipulation as well. Asa rule, cell cultures known to harbor an infectious etiologicagent should be manipulated in compliance with containmentmeasures recommended for the etiologic agent. With the exceptionof very well-characterized cell cultures for which theuse of a type II biosafety cabinet depends on the origin of thecells, work with cell cultures from human or primate originshould generally and minimally be performed under containmentlevel 2 using a type II biosafety cabinet. In every case,containment measures should minimize adventitious contaminationof the cell cultures and offer a maximal protection ofhuman health and the environment.
Keywords: Activity; an; Animal; AS; assessment; at; biosafety; Case; cell culture; cells; compliance; containment; environment; EVALUATION; general; genetic modification; hazard; health; Human; human health; IS; LEVEL; measure; measures; ON; ORIGIN; pathogen; pathogenic; recommendation; Recommendations; Reduction; Research; result; risk; Risk Assessment; risks; SBB; Type; use; work